2015
DOI: 10.1590/s0080-623420150000400016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of web-based electrocardiography simulation on strategies and learning styles

Abstract: Objective:To identify the association between the use of web simulation electrocardiography and the learning approaches, strategies and styles of nursing degree students. Method: A descriptive and correlational design with a one-group pretestposttest measurement was used. The study sample included 246 students in a Basic and Advanced Cardiac Life Support nursing class of nursing degree. Results: No significant differences between genders were found in any dimension of learning styles and approaches to learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
(31 reference statements)
1
17
1
3
Order By: Relevance
“…The results of this quasi-experimental study indicated that both traditional and virtual methods have increased students’ knowledge about cardiac dysrhythmia, but the virtual education method has had a greater impact. In the results, it must be mentioned that both groups indicated no significant difference in the level of knowledge in the pre-intervention stage, which is consistent with the findings of many other previous studies such as the study of Mohammadi et al ,[30] Baghaei et al ,[32] and Granero et al [8] Reviewing the research population of this study and its related literature, it can be accepted that nursing students in the pre-intervention phase did not have much knowledge about the subject. In addition, lack of any difference between the two groups was an indication of similarity between the two groups of virtual and traditional education in the present study and above-mentioned ones.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this quasi-experimental study indicated that both traditional and virtual methods have increased students’ knowledge about cardiac dysrhythmia, but the virtual education method has had a greater impact. In the results, it must be mentioned that both groups indicated no significant difference in the level of knowledge in the pre-intervention stage, which is consistent with the findings of many other previous studies such as the study of Mohammadi et al ,[30] Baghaei et al ,[32] and Granero et al [8] Reviewing the research population of this study and its related literature, it can be accepted that nursing students in the pre-intervention phase did not have much knowledge about the subject. In addition, lack of any difference between the two groups was an indication of similarity between the two groups of virtual and traditional education in the present study and above-mentioned ones.…”
Section: Discussionsupporting
confidence: 90%
“…The virtual method could increase students’ knowledge regarding cardiac dysrhythmia more than the traditional method. The results of this study are correspond to those of Chang and Hsu[40] and Granero-Molina et al ,[8] which indicated a significant difference after intervention in virtual method, while the results of the study by Badanara et al indicated the effectiveness of the traditional method,[41] which is incompatible with the results of this study. Although various studies report the success of the virtual education method, it should also be noted that this type of training for independent and self-governing students who are more intended to these learning strategies is more effective naturally.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…2,3 Consequently, regardless of their expertise, nurses are expected to be competent in electrocardiogram (ECG) rhythm recognition. 1,2,[5][6][7] Nonetheless, this is not always the case and research suggests that qualified nurses often lack competence in ECG rhythm recognition. [8][9][10][11] In many countries, nursing education does not include a final licensing examination, which means that nurses are allowed to practise without supervision immediately after completing their undergraduate programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Granero-Molina et al 34 using an electrocardiogram simulation in a Web environment, it was possible to stimulate the theoretical learning style, which aims to understand the theory before the practice, and the pragmatic style, where how to apply the knowledge in the real world is what it is necessary to know. The "ECG Fácil" app supplies theoretical information about ECG interpretation on opening the first tabs and then uses clinical cases, aiming to illustrate the application of knowledge to clinical practice.…”
mentioning
confidence: 99%